ANALISIS PENGGUNAAN LAPISAN TANAH PENUTUP SEBAGAI MATERIAL PERKERASAN JALAN ANGKUT TAMBANG DI PT. KARYA SUMBER ALAM PERKASA, KABUPATEN SANGGAU, KALIMANTAN BARAT - Annisa Agusfibrianti; Budhi Purwoko; Hendri Sutrisno (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
PT. Karya Sumber Alam Perkasa is a mining company of granite commodities located in Pandan Sembuat Village, Tayan Hulu District, Sanggau Regency, West Kalimantan that uses hauling road pavement materials from other locations, so this research is carried out by testing the feasibility of using overburden to be used as hauling pavement material in pit three where the mining will be carried out. This research by taking three samples of disturbed soil in the field randomly for testing in the laboratory related to the physical properties (specific gravity, sieve analysis, hydrometer, liquid limit, plastic limit), compaction and soaking CBR to obtain results that become the parameters according the specification so the conclusions drawn regarding the feasibility if the sample to be a houling road pavement material.The result of this research are in the AASHTO classification the first sample is in A-7-6 group, the second sample is in A-7-5 group while the third sample in A-2-6 group, in the Van Der Merwe Limitation for the first and the second sample are in the same class which is medium, while the third sample is in the low class. The immersion CBR values for the first, second, and third samples were 1,791%, 0,448%, and 5,663% so that all three samples are not suitable to be used as road pavement material for hauling road at PT. KSAP because it can’t fulfil some conditions which are the provisions in its specification.